Population Parasitoid of Larva in Different Planting Period in Tandem Hulu Plantation Land of PTPN II Sei Semayang - Elfrida Sari Sinaga; Maryani Cyccu Tobing; Lisnawita Muis (Jurnal Agroekoteknologi, 2019)
Parasitoids have been introduced in PTPN II Sei Semayang to control various pests that attack the crops.This research aims to determine the diversity of parasitoid species in sugarcane fields. This research was carried out at Central research and Development of Sugarcane Crop Sei Semayang PTPN II. The method of this research used Randomized Block Design non factorial which consists of 6 planting periods (block):early April (block I), early May (block II), early June (block III), end of April (IV), end of May (V),and end of  June (VI) with eight replications.The results showed that Apanthales flavipes was a parasitoid found in the field with different amounts at each block. Block I was 212 populatios, block II was 218 populations, block II was 266 populations, block IV was 187 populations, block V 194 populations, and block VI 348 populations. The highest percentage of a A. flavipes parasilization was found in block VI 1.25% and lowest percentage in block I 0.75%. The sex ratio of  parasitoids : 406 males and 1019 females.